Vitamin A, Nutrition, and Health Values of Algae: Spirulina, Chlorella, and Dunaliella - Tang, Guangwen; Suter, Paolo M. (Journal of Pharmacy and Nutrition Sciences, 2011)
Spirulina, chlorella, and dunalliella are unicellular algae that are commercially produced worldwide. These algae are concentrated sources of carotenoids (especially provitamin A carotenoids) and other nutrients, such as vitamin B12. Their health benefits as a complementary dietary source for macro and micro nutrients have been studied and confirmed in various populations. The safety of human consuming these algae and products derived from these algae by humans has been widely studied. It is generally concluded that these algae and its products are safe if cultivated properly in a non-contaminated environment, and if consumed in moderation.